Efficacy and safety of omalizumab therapy in urticaria vasculitis - Petrelli, Fiorella; Giannini, Daiana; Bilia, Silvia; Del Corso, Isabella; Rocchi, Valeria; Migliorini, Paola; Puxeddu, Ilaria (Frontiers in Allergy, 2022)
Urticarial vasculitis (UV) is a small-vessel leukocytoclastic vasculitis characterized by different clinical manifestations ranging from long-lasting urticarial lesions to severe and potentially life-threatening multi-organ involvement. Omalizumab (OMA), anti-IgE recombinant humanized IgG1 monoclonal antibody, has been successfully used to treat few cases of severe and/or refractory UV. In this study we report our experience on 6 patients with refractory normocomplementemic UV successfully treated with anti-IgE therapy (OMA), suggesting that this biological therapy may be a safe and effective therapeutic option in UV.